(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
The study was carried out to examine the Pb concentrations of water, sediment and soil of Shitalakhya River at Polash and Ghorashal areas in Bangladesh. The ranges of Pb in water, sediments, soils and vegetables like pumpkin leaves and alligator weeds were found 1.87 - 49.08, 8.49 - 75.81, 19.68 - 85.13, 1.08 - 3.92 and 1.18 - 4.22 mg/kg, respectively. The lead concentrations of surface water, sediment and soil samples were within the safe limit of different international standard except samples of the point source of urea fertilizer factory. The highest concentrations of Pb in alligator weeds and pumpkin vegetable leaves were recorded 3.92 and 4.224 mg/kg, respectively at the point source of urea fertilizer factory. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 91-99, 2016